Is there value in routine administration of outcome questionnaires? - Agel, Julie; Bransford, Richard (Evidence-Based Spine-Care Journal, 2012)
Study design: Retrospective case-series of prospective routinely collected Short Form 36v2 (SF-36v2) data in an outpatient spine clinic.Objective: To determine if there is value in routine administration of outcome questionnaires for the patient and/or clinician without a targeted population or monitoring of follow-up.Method: Retrospective review of Health Outcomes Scoring database.Results: During an 18-month period 1,863 patients completed 3,124 SF-36v2 questionnaires. The extent of diagnoses and the uneven timing of follow-ups of the completed questionnaires render this data useless both to the patient and for aggregate analysis.Conclusion: There is no value in routine administration of outcome questionnaires to patient care or clinical research.